The Effect of PLA/HA Coating Thickness on Crack Formation and Corrosion Performance - Mas Ayu, Hassan; Zubaidah, Zamri; Rosdi, Daud; Norizah, Redzuan; Izman, Sudin (Springer, Cham, 2022)
Surface modification of metallic implants is often required to facilitate positive interaction between the implant and the surrounding hard tissue. In this study, a polymer-ceramic composite coating of polylactic acid/hydroxyapatite (PLA/HA) was successfully deposited on a Co–Cr–Mo alloy by the dip coating method in chloroform suspension at room temperature. The effect of various PLA/HA dipping layers was studied and the dip coating process parameters were optimized in order to obtain a homogeneous, crack free, densely packed and adhesive coating. It is found that PLA/HA-coated substrate with 3 dipping layers were denser and less crack sensitive compared to 6 dipping layers. Although it is hypothesized that a coarser coated surface helps to facilitate ingrowth of osseous tissue in human body, but current findings show opposite manners due to the fact that a higher corrosion rate was obtained. The coated substrate with 6 dipping layers also were found more profound to micro-cracks and delamination with a lower microhardness value compared to coated substrate with 3 dipping layers.